2016
DOI: 10.1016/j.bbadis.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral biomarkers of stroke: Focus on circulatory microRNAs

Abstract: Stroke is the second leading cause of death in the world. Stroke occurs when blood flow stops, and that stoppage results in reduced oxygen supply to neurons in the brain. The occurrence of stroke increases with age, but anyone at any age can suffer from stroke. Recent research has implicated multiple cellular changes in stroke patients, including oxidative stress and mitochondrial dysfunction, inflammatory responses, and changes in mRNA and proteins. Recent research has also revealed that stroke is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 84 publications
0
53
0
Order By: Relevance
“…MiRNAs are a class of naturally occurring short non-coding RNAs that regulate the expression of a wide range of genes and play an important role in various biological functions including cell differentiation, development, immune responses, metabolism, and carcinogenesis [8][9][10]. Prior studies indicate miRNA are dysregulated in the blood and brain of rodent ischemic stroke [11][12][13][14]. In addition, several miRNAs including miR-21, miR-210 and miR-223, et al were reported as the biomarkers for ischemia stroke [15][16][17][18][19].…”
Section: Original Papermentioning
confidence: 99%
“…MiRNAs are a class of naturally occurring short non-coding RNAs that regulate the expression of a wide range of genes and play an important role in various biological functions including cell differentiation, development, immune responses, metabolism, and carcinogenesis [8][9][10]. Prior studies indicate miRNA are dysregulated in the blood and brain of rodent ischemic stroke [11][12][13][14]. In addition, several miRNAs including miR-21, miR-210 and miR-223, et al were reported as the biomarkers for ischemia stroke [15][16][17][18][19].…”
Section: Original Papermentioning
confidence: 99%
“…MiR-208a can be seen very rapidly in the bloodstream after AMI, providing a quick diagnostic tool (Wang et al, 2010). Several studies have found circulating miRNAs change following stroke in humans (Vijayan et al, 2016). In atherosclerosis, administering miR-126 apoptotic bodies leads to improved vasculature by increasing the production of chemokine CXCL12, leading to increased migration of endothelial progenitor cells to the impacted area (Zernecke et al, 2009).…”
Section: Micrornas In Specific Tissues and Disease Processesmentioning
confidence: 99%
“…It has been demonstrated that a number of proteins, such as calcium binding protein B (S100B), myelin basic protein, neuron-specific enolase, and glial fibrillary acidic protein, are related to ischaemic injury. Hundreds of genes may have an impact on stroke pathogenesis or are associated with risk factors [8]. However, their specificity and ability to distinguish among different phases of stroke, especially the hyperacute phase, or symptoms resembling stroke is uncertain [9].…”
Section: Introductionmentioning
confidence: 99%